Angular Stable Miniplate Fixation of Chronic Unstable Scaphoid Nonunion - Schormans, Philip M. J.; Brink, Peter R. G.; Poeze, Martijn; Hannemann, Pascal F. W. (Journal of Wrist Surgery, 2018)
Background Around 5 to 15% of all scaphoid fractures result in nonunion. Treatment of long-lasting scaphoid nonunion remains a challenge for the treating surgeon. Healing of scaphoid nonunion is essential for prevention of scaphoid nonunion advanced collapse and the subsequent predictable pattern of radiocarpal osteoarthritis.Purpose The purpose of this study was to investigate the feasibility of fixation of the scaphoid nonunion with a volar angular stable miniplate and cancellous bone grafting. We hypothesized that this technique could be successful, even in patients with previous surgery for nonunion and in patients with a long duration of nonunion.Patients and Methods A total of 21 patients enrolled in a single-center prospective cohort study. Healing of nonunion was assessed on multiplanar computed tomography scan of the wrist at a 3-month interval. Functional outcome was assessed by measuring grip strength, range of motion, and by means of the patient-rated wrist and hand evaluation (PRWHE) questionnaire.Results During follow-up, 19 out of 21 patients (90%) showed radiological healing of the nonunion. The range of motion did not improve significantly. Postoperative PRWHE scores decreased by 34 points. Healing occurred regardless of the length of time of the nonunion (range: 6–183 months) and regardless of previous surgery (38% of patients).Conclusion Volar angular stable miniplate fixation with autologous cancellous bone grafting is a successful technique for the treatment of chronic unstable scaphoid nonunion, even in patients with long-lasting nonunion and in patients who underwent previous surgery for a scaphoid fracture. Rotational interfragmentary stability might be an important determining factor for the successful treatment of unstable scaphoid nonunion.Level of Evidence Level IV.
Keywords: scaphoid nonunion; internal fixation; plating